STRATEGI DINAS KESEHATAN DALAM MENEKAN PENURUNAN STUNTING DI KABUPATEN SUMBAWA (Stusi Kasus Kecamatan Moyo Utara dan Kecamatan Sumbawa) - Sherli Wardanny; Aldi Apriansyah (Pusat Riset dan Publikasi, 2026)
Stunting is a public health problem that remains a serious challenge in Indonesia, including in Sumbawa Regency. Although various policies and programs have been implemented, the prevalence of stunting in Sumbawa Regency shows fluctuations and has not experienced a sustained decrease. This study aims to analyze the strategies of the Sumbawa District Health Office in reducing the decline in stunting and to identify the challenges faced in its implementation, particularly in Moyo Utara District and Sumbawa District as areas with relatively high stunting prevalence. This study uses a qualitative approach with a case study method. Data collection techniques were carried out through in-depth interviews, observations, and documentation studies, while data analysis was conducted descriptively and qualitatively. The research results indicate that the Sumbawa District Health Office's strategies include strengthening specific and sensitive nutrition interventions, optimizing basic health services through integrated service posts (posyandu) and the First 1,000 Days of Life (HPK) program, cross-sector collaboration, and utilizing data-based nutrition information systems. However, the implementation of this strategy still faces various challenges, including limited human resources in nutrition, low public participation and awareness, as well as disparities in access to health services in rural areas. This study concludes that the success of reducing stunting requires strengthening cross-sector coordination, increasing resource capacity, and empowering the community sustainably.